Normas aplicables a las partes contratantes que incumplan injustificadamente los contratos internacionales de mercancías. - Ortega Barragan, Maria Alexandra (My University, 2019)
The present case study exhibits the applicable norms and the possible solutions to which there can receive the parts that are linked in the contracts internationally of goods, that is to say, the contractual relation that exists so much between the seller as the buyer in the moment itself to trade. As resource for the efficient development of the present investigation has been appealed to the use of a qualitative methodology, being based on index-linked magazines. Since it demonstrates the investigation the juridical fundamental base has been identified as it it is the Convention of the United Nations by the contracts of International sale of Goods and beginning of the UNIDROIT; also it has been used as support to such legal bodies as: Organic code of the Production I Trade and Investments (COPCI), Civil Ecuadorian Code, Constitution of the Republic of the Ecuador, Regulation (CE) Nº 593/2008 of the European Parliament and of the Advice on the law applicable to the contractual obligations (Rome I), Organic Law for the Productive Promotion, Attraction of Investments, Generation of Employment, and Stability and Fiscal Balance and the Regulation of Arbitration of the Convention of the United Nations on the contracts of International sale of Goods, which has allowed to know the procedure that it is necessary to do to raise the demand in case of unjustified nonperformance of international contract of goods.
El presente estudio de caso expone las normas aplicables y las posibles soluciones a las que se pueden acoger las partes que se encuentran vinculadas en los contratos internacional de mercancías, es decir, la relación contractual que existe tanto entre el vendedor como el comprador en el momento mismo de comerciar. Como recurso para el desarrollo eficiente de la presente investigación se ha recurrido a la utilización de una metodología cualitativa, basándose en revistas indexadas. Como demuestra la investigación se ha identificado la base jurídica fundamental como lo es la Convención de las Naciones Unidas sobre los Contratos de Compraventa Internacional de Mercaderías y los principios de la UNIDROIT; también se ha usado como apoyo a cuerpos legales tales como: Código Orgánico de la Producción Comercio e Inversiones (COPCI), Código Civil Ecuatoriano, Constitución de la República del Ecuador, Reglamento (CE) Nº 593/2008 del Parlamento Europeo y del Consejo sobre la ley aplicable a las obligaciones contractuales (Roma I), Ley Orgánica para el Fomento Productivo, Atracción de Inversiones, Generación de Empleo, y Estabilidad y Equilibrio Fiscal y el Reglamento de Arbitraje de la Convención de las Naciones Unidas sobre los Contratos de Compraventa Internacional de Mercaderías, lo cual ha permitido conocer el procedimiento que se debe hacer para plantear la demanda en caso de incumplimiento injustificado de contrato internacional de mercancías.
Keywords: CONTRATO; CONVENIO DE VIENA; COMPRAVENTA INTERNACIONAL; PARTES CONTRATANTES.